INFORMATION SYSTEM DESIGN FOR MICRO CREDIT BANKS - Linda Wahyu Widianti (STMIK Jakarta, 2003)
Developments in the banking system under its wings for small entrepreneurs (market traders)who very much and is the economic backbone of the people in Indonesia. To assist the smallentrepreneurs who are usually very shy in touch with the bank. This micro-service productsin its implementation constitute a computer-based information systems and managementprocesses utilize information technology as a tool for data processing.Information system used for the calculation of return on a loan and is available at this microservice are semi automatic because many feel That matter deficiencies. These deficiencies,among others, is not effective when used in making the loan payment calculation reportscustomers, it is disturbing performance in a billing clerk.Micro-services information system design of the proposed implementation will be realizedusing a computer. This system can provide advantages such as speed up the preparation ofreports and more secure data storage, so it can provide accurate and reliable information thatwill ultimately produce an effective performance and efficient performance in supporting thedecision making process for its users